The Martian chronicles - Bradbury, Ray, 1920- (New York : Bantam Books, 1979)
Chronicles the early attempts by humans to colonize an inhabited Mars by transforming the Red planet into a mirror image of the world they left behind.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
Booklist, August 1997.
Notable/Best Books (A.L.A.), April 2011.
Wilson's Junior High School, September 1995.
Keywords: Space colonies -- Fiction; Science fiction; Space colonies -- Fiction; Mars (Planet) -- Fiction; Mars (Planet) -- Fiction; Science fiction